Aplikasi Irigasi Tetes Bertingkat Dengan Tanaman Horti Kultura di Perumahan Padat Penduduk Kota Mataram Hulu: Application Of Dropping Irrigation With Horti Culture in Solid Population Housing in Mataram Hulu City - I Dewa Gede Jaya Negara; Bambang Hariyanto; Anid Supriyadi (LPPM Universitas Mataram, 2022)
This study aims to determine the application of a three-storey drip irrigation system to horticultural crops of chilies, kale and eggplant as one of the household food supporting crop commodities. In addition to increasing the potential for irrigation and boosting the economy from agricultural products on this limited land, it is necessary to know this, so that it can be used as material for consideration in maintaining family food security. Irrigation test activities were also carried out on irrigation uniformity, irrigation distribution and irrigation depth at various irrigation times. Tests were carried out on variations of soil and compost as planting media with the ratios of: 70%: 30%, 50%: 50%, 30%: 70% and four variations in tank water volume. The drip application network uses ½” PVC pipe and dripe on the third floor, while for the first and second levels the Netafim (NTF) pipe is 12 mm. The secondary irrigation network uses ¾ inch, 1 ½ inch and ½ inch PVC in an irrigation test chamber measuring 1.5 m x 4 m and a height of 1 m between levels. The results of the analysis of the test data showed that the uniformity of PVC drip irrigation and NTF combined obtained an average of above 95%, with a very even distribution of water. Irrigation depth obtained at all variations of the water tank level, that is, at 70% of the soil ranges from 3cm -20 cm, at 50% of the soil ranges from 4cm - 20cm and at 30% the amount of infiltration ranges from 2.5 cm - 18.5 cm. Multilevel drip irrigation can support the provision of family food in meeting the needs of kitchen ingredients such as chilies and vegetables to support family food security